2004
DOI: 10.1074/jbc.m313665200
|View full text |Cite
|
Sign up to set email alerts
|

Divergence in Noncognate Amino Acid Recognition between Class I and Class II Lysyl-tRNA Synthetases

Abstract: Lysine insertion during coded protein synthesis requires lysyl-tRNA Lys , which is synthesized by lysyl-tRNA synthetase (LysRS). Two unrelated forms of LysRS are known: LysRS2, which is found in eukaryotes, most bacteria, and a few archaea, and LysRS1, which is found in most archaea and a few bacteria. To compare amino acid recognition between the two forms of LysRS, the effects of L-lysine analogues on aminoacylation were investigated. Both enzymes showed stereospecificity toward the L-enantiomer of lysine an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 41 publications
2
40
0
Order By: Relevance
“…Intein-tagged proteins were purified on a chitin affinity column (New England Biolabs) and stored in 25 mM Tris-HCl, pH 8.0, 150 mM NaCl, 4 mM 2-mercaptoethanol, 20% glycerol. E. coli BL21(DE3)/pQE31-Ec-lysS and E. coli BL21(DE3)/pQE31-Ec-pheS-pheT were used to prepare lysyltRNA synthetase and phenylalanyl-tRNA synthetase, respectively (16,17). Native tRNAs were purchased from Chemical Block (Moscow, Russia).…”
Section: Methodsmentioning
confidence: 99%
“…Intein-tagged proteins were purified on a chitin affinity column (New England Biolabs) and stored in 25 mM Tris-HCl, pH 8.0, 150 mM NaCl, 4 mM 2-mercaptoethanol, 20% glycerol. E. coli BL21(DE3)/pQE31-Ec-lysS and E. coli BL21(DE3)/pQE31-Ec-pheS-pheT were used to prepare lysyltRNA synthetase and phenylalanyl-tRNA synthetase, respectively (16,17). Native tRNAs were purchased from Chemical Block (Moscow, Russia).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies indicated that LysRS1 and LysRS2 are markedly different in their abilities to discriminate lysine analogues (18). For example, the competitive inhibitor AEC has a K i for the aminoacylation reaction that is several hundred-fold lower for LysRS2 than LysRS1.…”
Section: Substrate Discrimination By Lysrs1 Variantsmentioning
confidence: 99%
“…Aminoacylation was performed at 37 °C in 100 mM Hepes (pH 7.2), 25 mM KCl, 10 mM Sample disks were washed and radioactivity counted as described previously (18). The steady-state kinetic parameters given represent the average of at least two independent experiments where values deviated by no more than 10% between individual determinations.…”
Section: Aminoacylation Assaysmentioning
confidence: 99%
See 2 more Smart Citations